Strategi Pengembangan Desa Wisata Mondu Berbasis Masyarakat Di Kabupaten Sumba Timur - Junaedin Wadu; Febyningsi Rambu Ladu Mbana (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Sumba Island, one of the most beautiful islands in the world, is a good choice for traveling because it has a variety of natural and cultural tourist attractions that attract tourists, one of which is Mondu Village, East Sumba Regency. However, this potential has not yet been optimized to improve the local community's economy. This research aims to analyze the internal factors (strengths and weaknesses) and the external factors (opportunities and threats) in the development of the Mondu Tourism Village and formulate a strategy for community-based development of the Mondu Tourism Village. This research is exploratory, with 13 informant sources determined using the purposive sampling method, considering that the informant sources can represent and understand internal and external factors affecting the development of the Mondu Tourism Village. The data collection method uses Focus Group Discussion (FGD). Data analysis uses SWOT analysis to create an IFE, EFE, IE matrix, SWOT matrix, and QSPM to establish strategic priorities. The study results show that the internal factor, which is the main strength in developing the Mondu Tourism Village, is its diverse natural tourism potential. The main weakness is that community creativity is still minimal. The external factor that is an opportunity is the development of technology and information as promotional media, and the threat is that young people tend to look for work in the city. The priority strategy with the highest TAS score is educating the public about the management of tourist attractions and education about tourist attractions. So, it is recommended that counseling and capacity development be carried out regarding knowledge of tourist attractions and increasing the community's creative economy to improve the economy.